Two magnon scattering and anti-damping behavior in a two-dimensional epitaxial TiN/Py(tPy)/β-Ta(tTa) system. Issue 14 (23rd January 2017) - Behera, Nilamani; Kumar, Ankit; Chaudhary, Sujeet; Pandya, Dinesh K.
Abstract : Anti-damping in two-magnon scattering free two-dimensional epitaxial Si(400)/TiN(200) (8 nm)/Py(200) (12 nm)/Ta(200) (6 nm) system. Abstract : The prime requirements for the spin transfer torque based ferromagnetic (FM)/nonmagnetic (NM) bilayer spin devices are (i) the absence of two-magnon scattering (TMS) noise, (ii) minimum energy dissipation and (iii) fast switching. To realize these objectives we have studied the thickness, Py (permalloy) thicknesses ( t Py ) and β-Ta thicknesses ( t Ta ), dependent magnetization dynamics behaviour of the epitaxial Py ( t Py = 3–20 nm)/β-Ta ( t Ta = 1.5–15 nm) system. The t Py dependence of TMS in epitaxial Py nano-layers ( t Py = 3–20 nm) grown on a Si(400)/TiN(200) (8 nm) substrate is explored in terms of uniform and non-uniform magnetization precession regimes by employing ferromagnetic resonance field ( H r ), line-width (Δ H ), and Gilbert damping constant ( α ) behaviour. It is found that in Py, t Py < 10 nm, layers TMS is dominating due to non-uniform precession of the magnetization. However in Py, t Py ≥ 10 nm, layers the uniform magnetization precession dominates, therefore Py layers, t Py ≥ 10 nm, are almost free from TMS. Furthermore, a nearly TMS free 12 nm epitaxial Py(200) layer is capped with β-Ta ( t Ta = 1.5–15 nm) layers to explore the t Ta dependent magnetization precession of epitaxial Py (12 nm) in terms of change in effective Gilbert damping constant ( α eff ). An anomalous decrease in α eff from 0.0087 at t Ta = 0 to a minimum value of 0.0077 at t Ta = 6 nm, and its subsequent increase for t Ta > 6 nm are observed in the epitaxial Py (12 nm)/β-Ta( t Ta ) system. Therefore the Si(400)/TiN(200) (8 nm)/Py(200) (12 nm)/β-Ta(200) (6 nm) epitaxial system with nearly uniform magnetic precession and minimum effective Gilbert damping is suitable for low energy loss and ultrafast switching applications in spin transfer torque devices.